Problem Identification in Planning Transport Process of Break Bulk Cargo - Iwona KRZYŻEWSKA (Communications of International Proceedings, 2021)
The break bulk cargo system involves the transport of independent consignments using grouped means of transport. The cargo is not divided up during reloading. Its content can be dimensioned and weighed. Separate consignors are handled in the course of one transport task. Planning the transport process requires a focus on aspects related to both the process itself and the accompanying elements. In order to meet the customer's expectations, attention should be paid to the proper planning of activities that are related to the transport. Important problems in organization of transport process are: insufficient knowledge of employees, selection of an adequate means of transport, calculate relevant transport time, lack of IT solutions that support the transport process. The aim of this study is to identify problems and their solutions in the organisation of the break bulk cargo process.
Keywords: Transport; Break Bulk; Problem; Solution; Process.